2019
DOI: 10.3390/en12152975
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Multi-Vane Expanders in ORC Systems—A Review on the Experimental and Modeling Research Activities

Abstract: This paper reviews the applications of the multi-vane expanders in ORC (organic Rankine cycle) systems. The operating principle and design of the ORC systems are addressed in the introduction. Then, there is a brief review of the expanders applied in small-power and micro-power ORCs, and a discussion of the multi-vane expander design and operating principle as an introduction to a comprehensive review on the applications of the multi-vane expanders in ORC systems. The different features of the multi-vane expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…Figure 26 shows the components of a vane expander. Based on the available literature [156][157][158][159], it can be stated that vane expanders are devices on a rather smaller scale. The maximum currently available units, when coupled with the ORC system, reach the power of 7.5 kW.…”
Section: Vane Expandersmentioning
confidence: 99%
“…Figure 26 shows the components of a vane expander. Based on the available literature [156][157][158][159], it can be stated that vane expanders are devices on a rather smaller scale. The maximum currently available units, when coupled with the ORC system, reach the power of 7.5 kW.…”
Section: Vane Expandersmentioning
confidence: 99%
“…Research and development studies on this type of domestic power systems are carried out in different research and development units around the world [25], including the Department of Thermodynamics and Renewable Energy Sources of Wrocław University of Science and Technology. The integration of a gas central heating boiler with a power generating unit is usually done by redesigning the boiler into a home CHP micro power plant.…”
Section: Fuel Typementioning
confidence: 99%
“…Therefore, they fit better to small scale ORCs. Piston [55][56][57][58][59][60][61], screw [62][63][64][65][66], scroll [67][68][69][70][71][72][73], lobe [74,75] and multi-vane [25] expanders can be applied in domestic ORCs. These expanders are at different stage of development.…”
Section: Design Considerations and Comparison Of Different Domestic Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Piotr. K [6] presented a review study on the multi-vane expander applications. It was concluded that it is suitable for limited applications with low cost for manufacturing and it can work in low pressure.…”
Section: Introductionmentioning
confidence: 99%